(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This research article investigates the intricate correlation between regular physical exercise, cognitive performance, and the psychological health of students within the modern educational framework. As academic curricula become increasingly demanding, the integration of physical movement is often sidelined, leading to a rise in sedentary-related cognitive decline and mental fatigue. This study utilizes a quantitative and qualitative approach to demonstrate how physical activity enhances neuroplasticity and emotional regulation. The findings reveal that students who engage in consistent physical exertion demonstrate superior memory retention, higher Grade Point Averages (GPA), and significantly lower levels of psychological distress.